Hannah Steiner: capstone - Steiner, Hannah, artist (Colorado State University. Libraries, 2013)
The artist's statement: Cancer cells are complex growths that produce enormous physical, mental and emotional damage. They are a manifestation of the sublime- the combination of terror and beauty. This contradiction is seeing the beauty in what destroys. Translating that experience into sculpture is the foundation of my work. My sculpture is a means of understanding ideas through material manipulation. The material and subject matter have contradictory associations. Fabric has a connection with comfort and the aesthetic of everyday life. Textiles are captivating and demanding Formal characteristics of composition, line, intensity, and form are another framework. Through these techniques, the domestic setting is also evoked- comfort and familiarity. They pose a challenge to organize a material into a rigid or pliable sculpture. Sewing, quilting, embroidery, dipping, modeling, stiffening, ribboning are techniques used to realize this contradiction. This challenge transforms into an entire embodiment of endless pursuit.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.